Efforts to Increase Community Participation in Supporting The Continuity of Ecotourism Development Policies - Tarino, Elza Novira; Purnomo, Eko Priyo (Jurnal Penelitian Pariwisata, 2024)
This research aims to identify strategies that enhance community participation in supporting the sustainability of ecotourism development policies. The study specifically explores how local communities can be involved in decision-making, implementation, benefit-sharing, and evaluation activities within ecotourism projects. The methodology used is a qualitative literature review, drawing on secondary data from sources such as journal articles, theses, government reports, and books relevant to community engagement and ecotourism. The results indicate that active community participation significantly improves the sustainability and success of ecotourism projects. By engaging local communities, ecotourism not only promotes environmental and cultural conservation but also brings economic benefits, such as job creation and income growth for local populations. In particular, the involvement of communities in planning and policy evaluation is essential for aligning ecotourism initiatives with local needs. The conclusion emphasizes that fostering community involvement through education and training is critical for empowering communities and ensuring the long-term sustainability of ecotourism projects. This research provides valuable insights for policymakers to create more inclusive and sustainable ecotourism development strategies. Keywords: ecotourism, policy, community